THE EXPRESSION OF POSSESSION IN SOME LANGUAGES OF THE EASTERN LESSER SUNDA ISLANDS - Philippe Grangé (Linguistik Indonesia, 2015)
The possessor-possessed, or “preposed possessor” syntactic order, has long been considered a typological feature common to many Eastern Lesser Sunda Islands, labelled either “Central-Malayo Polynesian languages” or “East Nusantara languages”, although these groupings do not exactly coincide. In this paper, the syntax and semantism of possession in some languages of the Eastern Lesser Sunda Islands are described. There is a wide variety of possession marking systems in the Eastern Lesser Sunda Islands, from purely analytic languages such as Lio to highly flexional languages such as Lamaholot. The morphological contrast between alienable and inalienable possession is widespread among the languages of this area. The study focuses on Lamaholot, spoken at the eastern-most end of Flores, and the three neighbouring islands of Adonara, Solor and Lembata. This language has a complex possessive system, involving suffixes, free morphemes, a specific preposition, and possessive pronouns, along with person agreement and morpho-phonological features. Lamaholot can be considered a highly representative example of East Nusantara languages.